Exploring the influence of an intercultural reading programme (IRP)in developing an intercultural framework among Malaysian secondary school students. - Mehar Singh, Manjet Kaur (Universiti Sains Malaysia, 2017)
The research investigated the level of intercultural knowledge and intercultural behavior through the Intercultural Reading PRogramme (IRP) incorporated into the English language syllabus of Form Four. The conceptual framework of this study incorporated the Schema Theory (Tierney & Pearson, 1994) and Reader Respond Theory (Mitchell, 2014). IRP consisted of four different phases (pre-intervention, intervention, post intervention and data analysis). Data was collected through qualitative and quantitative tools from 292 respondents who were Form Four national secondary school students in Penang.